Autofluorescence-guided surgery for the treatment of medication-related osteonecrosis of the jaw (MRONJ): a retrospective single-center study - Otto, Sven; Schnödt, Eva Maria; Haidari, Selgai; Brunner, Teresa Franziska; Aljohani, Suad; Mosleh, Mohamed; Ristow, Oliver; Tröltzsch, Matthias; Pautke, Christoph; Ehrenfeld, Michael; Fliefel, Riham (Oral surgery, oral medicine, oral pathology and oral radiology, 2021)
Objective - Medication-related osteonecrosis of the jaw (MRONJ) has become a serious concern for patients under antiresorptive treatment, especially in the oncological setting. Different approaches have been described in the management of MRONJ, including innovative autofluorescence-guided surgery. However, until now, there has been a lack of data regarding the outcome. In this study, we evaluated the efficacy of minimally invasive autofluorescence-guided resection in MRONJ. - Study Design - Seventy-five patients with 82 lesions were included in this retrospective, single-center study. All included patients were diagnosed with MRONJ according to the American Association of Oral and Maxillofacial Surgeons guidelines and underwent autofluorescence-guided surgery with a minimum follow-up of 3 months. The primary outcome was complete integrity of the mucosa and absence of bone exposure. - Results - The MRONJ stages were stage 0 (3.7%), stage 1 (3.7%), stage 2 (75.6%), and stage 3 (17%). Overall, complete mucosal healing of all lesions after the first surgery was 81.7% (67 of 82), whereas it was 90.2% (74 of 82) after revision surgery. - Conclusions - The study showed that autofluorescence-guided surgery is a safe and successful treatment option that can be considered for all stages of MRONJ.